What organizational and business models underlie the provision of spiritual care in healthcare organizations? An initial description and analysis. Issue 2 (3rd April 2022) - Antoine, Aja; Fitchett, George; Marin, Deborah; Sharma, Vanshdeep; Garman, Andrew; Haythorn, Trace; White, Kelsey; Greene, Amy; Cadge, Wendy
Abstract: Two-thirds of American hospitals have chaplains. This article explores the organizational and business models that underlie how chaplains are integrated into hospitals. Based on interviews with 14 chaplain managers and the 11 healthcare executives to whom they report at 18 hospitals in 9 systems, we identify three central findings. First, there is significant variation in how spiritual care programs are staffed and integrated into their hospitals. Second, executives and chaplain managers see the value of chaplains in terms of their quality of care, reliability and responsivity to emergent patient and staff needs, and clinical training and experience working within a complex environment. Third, few departments rely on empirical data when making decisions about staffing, tending instead to default to the budgetary status quo. These findings provide the basis for a larger more systematic study.